APAMARGAKSHARA IN THE MANAGEMENT OF CERVICAL EROSION – A PHARMACOLOGICAL REVIEW (International Journal of Ayurveda and Pharma Research, 2021)
Cervical erosion happens when cells that line the inside of cervix grow on the outside of cervix. That means the squamous epithelium of the cervix is replaced by columnar epithelium. Nowadays it is very common among women in reproductive age. The women with cervical erosion complaints of vaginal discharge, vulval itching, dyspareunia, low back ache etc. In the parallel medical field it is managed by electrocautery, cryotherapy and CO2 laser vaporization. This condition can be correlated with Garbhashayamukhagata Vrana or Karnini Yonivyapada. In Ayurveda, it is treated by Ksharakarma along with internal medications. Ksharakarma itself is sufficient to clear the wound and to promote the healing process. This reviewing is done to know the pharmacological effect of Ksharakarma using Apamarga Kshara. It concluded that the procedure (Ksharakarma) and the drug used to perform the procedure (Apamarga) have the capacity to enhance the reduction of severity of the condition and gradually lead to the complete cure of the same. It is due to the efficacy of Ksharakarma to clear the unhealthy epithelial cells and the presence of wound healing components like tannins, flavonoids, antioxidants etc. in Apamarga. In effect it has equivalent result as modern management, cost effective, easy procedure, brief procedure, no or less complications, less chances for the recurrence of the same.